ANALISIS EFEKTIVITAS PELAKSANAAN PASAR MURAH BULOG DALAM MENJAGA STABILITAS HARGA BERAS DI DKI JAKARTA - Proborini, Anita; Ekowati, Titik; Sumarjono, Djoko (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purpose of this research was to analyze : (1) the effectivity of Pasar Murah in terms of its rice quantity management; (2) the effectivity of Pasar Murah in terms of its rice quality management; (3) the effectivity of Pasar Murah in terms of its selling location; (4) the effectivity of Pasar Murah in terms of its implementation time; (5) the effectivity of Pasar Murah in terms of rice price management. The survey method was used to conduct this research and was distributed to 96 respondents from 6 villages in the Administration City of South Jakarta. This research used One sample t-test to analyze rice quantity management, chi-square test to analyze rice quality management, selling location, and also rice price management. Pasar Murah's implementation time was analyzed descriptively. The results showed that fourth-five Pasar Murah's management (80%) succeeded to meet the Perum Bulog expectation. Rice quantity management (20%) did not succeed in meeting Perum Bulog expectation. Based on this result, it can be concluded that in general, Pasar Murah Bulog has been implemented effectively.